Between-Limb Differences in Patellofemoral Joint Forces During Running at 12 to 24 Months After Unilateral Anterior Cruciate Ligament Reconstruction. Issue 7 (June 2020) - Sritharan, Prasanna; Schache, Anthony G.; Culvenor, Adam G.; Perraton, Luke G.; Bryant, Adam L.; Crossley, Kay M.
Background: Patellofemoral joint (PFJ) osteoarthritis may occur after anterior cruciate ligament reconstruction (ACLR). The mechanisms underpinning the development of PFJ osteoarthritis are not known but may relate to altered PFJ loading. Few studies have assessed PFJ loads during high-impact tasks, such as running, beyond the acute rehabilitation phase (ie, >12 months) after ACLR. Purpose/Hypothesis: The purpose was to compare between-limb joint angles, joint moments, and PFJ contact force during running in individuals at 12 to 24 months after unilateral ACLR. We hypothesized that peak knee flexion angle, knee extension moment, and PFJ contact force during stance would be lower in the ACLR limb compared with the uninjured limb. Study Design: Controlled laboratory study. Methods: A total of 55 participants (mean ± SD age, 28 ± 7 years), 12 to 24 months after ACLR, ran at a self-selected speed (2.9 ± 0.3 m/s). Measured kinematics and ground-reaction forces were input into musculoskeletal models to calculate joint moments and muscle forces. These values were subsequently input into a PFJ model to calculate contact force peak and impulse. Outcome measures were compared between the ACLR and uninjured limbs. Results: In the ACLR limb, compared with the uninjured limb, the PFJ contact force displayed a lower peak (ACLR, 6.1 ± 1.3 body weight [BW]; uninjured, 6.7 ± 1.4 BW; P < .001) and impulse (ACLR, 0.72 ± 0.17 BW*seconds [BWs]; uninjured, 0.81 ± 0.17 BWs; P < .001). At the time of the peak PFJ contact force, the knee extension moment was lower in the ACLR limb (ACLR, 14.0 ± 2.4 %BW*height [%BW*HT]; uninjured, 15.5 ± 2.5 %BW*HT; P < .001). The opposite was true for the ankle plantarflexion moment (ACLR, 12.1 ± 2.6 %BW*HT; uninjured, 11.5 ± 2.7 %BW*HT; P = .019) and the hip extension moment (ACLR, 2.3 ± 2.5 %BW*HT; uninjured, 1.6 ± 2.3 %BW*HT; P = .013). The foot-ground center of pressure was located more anteriorly with respect to the ankle joint center (ACLR, 5.8 ± 0.9 %height [%HT]; uninjured, 5.4 ± 1.0 %HT; P = .001). No differences were found for the sagittal plane hip, knee, and ankle angles. Conclusion: The ACLR limb experienced lower peak PFJ loads during running, explained by a small anterior shift in the foot-ground center of pressure during stance that offloaded the torque demand away from the ACLR knee. Clinical Relevance: Lower net PFJ loading during running in the ACLR limb more than 12 months after ACLR suggests that underloading might play a role in the onset of PFJ osteoarthritis after ACLR.